The importance of the psychopedagogist in the learning difficulties of the employees of a higher education institution - Santos , Clecy Alves de Vasconcelos; Santos , Sérgio Ricardo Bezerra dos (Seven Editora, 2023)
The work is related to an analysis of the psychopedagogical action, carried out in a higher education institution. The objective was to analyze the barriers that hinder learning and the importance of the professional psychopedagogue as a facilitator in the process of understanding employees in relation to their goals and results. The methodology is descriptive and qualitative. The participants were employees from eight sectors of the college. The matrices of goals, competence and management reports were analyzed. Barriers were identified that generated difficulties in individual and institutional learning. It was suggested for the process of improvements in learning to outline the objectives of the institution, according to the methodology of Bloom's taxonomy, then apply the EOCMEA, and, through the inverted cone, make the analysis of the results, taking into account the bond that the collaborators demonstrate in the execution of the tasks presented. Finally, outline the appropriate interventions. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-082